Aqueous copper-mediated reversible deactivation radical polymerization (RDRP) utilizing polyetheramine derived initiators. Issue 34 (3rd August 2020) - Zhang, Jirui; Liarou, Evelina; Town, James; Li, Yongguang; Wemyss, Alan M.; Haddleton, David M.
Abstract : Polyetheramines (Jeffamines™) are used in Copper-mediated reversible deactivation radical polymeriation (Cu-RDRP) in water for the synthesis of temperature-responsive block copolymers. Abstract : Copper-mediated reversible deactivation radical polymeriation (Cu-RDRP) in aqueous media has been employed to synthesize temperature-responsive block copolymers, utilizing both hydrophobic and hydrophilic amide functional macroinitiators derived from polyetheramines (Jeffamines™). The in situ and rapid diproportionation of Cu(i )Br/Me6 TREN in water is exploited for the efficient homopolymerization of N -isopropyl acrylamide (NIPAM) and dimethyl acrylamide (DMA), at near full conversions (>99%), with low dispersity ( Đ < 1.18) and with a range of molar masses. The Jeffamine™-derived macroinitiators were used for both the synthesis of homopolymer and for one-pot chain extensions and block copolymerizations ( i.e. Jeffamine™-PNIPAM- b -PDMA). The obtained polymers exhibit controlled thermoresponsive aggregation behaviour which varies depending on the hydrophilicity/hydrophobicity of the macroinitiators and the composition of the block copolymers. Thermal analysis and dynamic light scattering (DLS) give an insight into the effect of these macroinitiators on the thermoresponsive aggregation behaviour of the synthesized polymers.